JUDGE'S JUDGMENT ON CRIMINAL OFFENSE AGAINST PERPETRATORS OF CRIMINAL EXTORTION WITH THE VIOLENCE AGAINST OTHER PEOPLE'S MOTORCYCLES (VERDICT STUDY NUMBER: 237/PID. B/2018/PN KLA) - Pramisela, Oktasari Putri; Hesti, Yulia (Progressive Law Review, 2020)
A crime or criminal act, usually perpetrators of criminals because of an encouragement based on the importance of fulfilling the necessities of life that is relatively difficult to fulfill. In principle the crime problem does not stand alone, but it relates to other issues such as social, economic, political and cultural which is as a phenomenon that affects each other. To tackle crimes and criminal acts such a thorough enforcement and anticipation policy is required. One of the most common criminal acts in the community is the violence of violent blackmail. Perpetrators can be assessed by the community, therefore it is necessary to be handled by the law enforcement officers intensively with the severity of the criminal that was dropped. The problem in this study is how the judge's consideration in dropping a criminal against perpetrators of criminal offenses with violence against motorcycles belonging to others, what are some factors causing perpetrators of criminal extortion with violence. The method of study used is the normative juridical approach and empirical approach obtained directly at the District Court of Kls II Kalianda, state Attorney of South Lampung. Based on the results of the study can be concluded that the judge's judgment in the criminal offence against the perpetrator of violent criminal offence is in accordance with the element contained in article 368 paragraph (1) of the criminal CODE and was sentenced to 2 years imprisonment. Factors affecting the cause of perpetrators of criminal extortion in violence are environmental factors, economic factors on society, the law enforcement. The advice given is to be expected to the Tribunal, the attorney general and the police in providing or establishing the article can be in accordance with its elements and actions, to the rationing punishment against the defendant is considered fair and give a deterrent effect so that the defendant can not repeat it again. There is cooperation between law enforcement and the community in minimizing the crimes that occurred.